Interaksi Antara Aplikasi Gelombang Suara Sonic Bloom dan Jenis Pupuk Cair Terhadap Jumlah dan Pembukaan Stomata serta Pertumbuhan Tanaman Jagung (Zea mays L.) - Mentari Putri Pratami; Sri Haryanti; Munifatul Izzati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Sonic bloom sound waves at a frequency of 3500-5000 Hz is able to stimulate the openedstomata which incrases the rate and efficiency of nutrients absorption that are applied through the leaves that are beneficial to the plant. By adding liquid organic and inorganic fertilizer as an effort to enhance the growth of cornplant. The purpose of this research is to know thesonic bloom application and liquid fertilizer to the growth of cornplant. This research was conducted in July until November 2014 in Laren village, sub district of Bumiayu, Brebes Regency and Laboratory structure and function of plant biology, FSM Diponegoro University. The arrangment used is the full factorial pattern of random design (RAL) with two factors, namely the sonic bloom application and liquid fertilizer. This research using six treatments, each of treatment are three replicates. The analysis of data used is Analysist of Variances (ANOVA), if it shows significant results then continued with the test duncan’s multiple test (DMRT)in fact 95% level. Parameters were observed such as number of stomata, the length and width of the opened stomata, height of plant, number of leaves,weight on fresh, weight on dry. The result showed that the application of sonic bloom real effect aganist the length and width of the opened stomata, number of leaves, weight on dry. By adding liquid fertilizer have the real effect of the lenght and width of the opened stomata, high of plants, weight on fresh, weight on dry. Furthermore giving of liquid organic fertilizer has more optimal result.Keywords :corn (Zea mays L.), sonic bloom, liquid fertilizer, stomata, growth.